A feasibility study of standard dressings versus negative-pressure wound therapy in the treatment of adult patients having surgical incisions for hip fractures: the WHISH randomized controlled trial. (1st March 2021) - Masters, James; Cook, Jonathan; Achten, Juul; Costa, Matt L.; ,
Abstract : Aims: This study sought to compare the rate of deep surgical site infection (SSI), as measured by the Centers for Disease Control and Prevention (CDC) definition, after surgery for a fracture of the hip between patients treated with standard dressings and those treated with incisional negative pressure wound therapy (iNPWT). Secondary objectives included determining the rate of recruitment and willingness to participate in the trial. Methods: The study was a two-arm multicentre randomized controlled feasibility trial that was embedded in the World Hip Trauma Evaluation cohort study. Any patient aged > 65 years having surgery for hip fracture at five recruitment centres in the UK was considered to be eligible. They were randomly allocated to have either a standard dressing or iNPWT after closure of the wound. The primary outcome measure was deep SSI at 30 and 90 days, diagnosed according to the CDC criteria. Secondary outcomes were: rate of recruitment; further surgery within 120 days; health-related quality of life (HRQoL) using the EuroQol five-level five-dimension questionnaire (EQ-5D-5L); and related complications within 120 days as well as mobility and residential status at this time. Results: A total of 462 valid randomizations were carried out (232 and 230 in the standard dressing and iNPWT groups, respectively). In the standard dressing group, 14 of 218 patients (6.4%) developed deep SSI. In the iNPWT group, four of 214 patients (1.9%) developed deep SSI. This gives a total rate of SSI of 4.2% (95% confidence interval (CI) 2.7% to 6.5%). Patients and surgeons were willing to participate in the study with 462 patients being recruited from a possible 749 (62.3%). Conclusion: The rate of deep SSI 30 days after surgery for a fracture of the hip was 4%, which makes a study comparing the clinical effectiveness of standard dressings and iNPWT feasible. Cite this article: Bone Joint J  2021;103-B(4):755–761.